Futures thinking in the University Library Diliman an analysis of the collective perception of future scenarios until 2025 - Rubio, Viktor Kevin S. (School of Library and Information Studies, University of the Philippines Diliman, 2016)
Futures Thinking is a method of envisioning possible futures that an organization could face both in its forthcoming years. This thesis conducted a Futures Thinking study in the University Library Diliman in an effort to contribute to its strategic efforts by presenting to its librarians a set of 26 future scenarios that the Associate of College and Research Librarians (ACRL) developed in 2010. The 26 scenarios were based from upcoming trends and changes in society that would affect all academic libraries. These hypothetical scenarios are evaluated by respondent librarians regarding their a) probability of occurence, b) impact if it were to occur, c) speed at which it might occur, and d) whether they perceive it as an opportunity or as a threat to their academic library.